2014
DOI: 10.4097/kjae.2014.66.3.195
|View full text |Cite
|
Sign up to set email alerts
|

A method for optimal depth of the nasopharyngeal temperature probe: the philtrum to tragus distance

Abstract: BackgroundThe nasopharyngeal temperature probe should be placed in the upper nasopharynx to reflect accurate core temperature. However, there have been no studies conducted to predict parameters for the optimal depth of the nasopharyngeal temperature probe. The purpose of this study was to examine the correlation between the optimal depth to the upper nasopharynx and the distance from the philtrum to the tragus and height.MethodsTwo hundred patients (100 females and 100 males) were enrolled in the study. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 8 publications
7
17
0
Order By: Relevance
“…The 9.40 (SD, 0.64) cm mean insertion depth to the posterior nasopharyngeal wall in our study is in accordance with an earlier study measuring the insertion depth for a nasopharyngeal temperature probe [ 16 ]. Previously published guidelines described a similar insertion depth between 9 and 10 cm [ 6 ], while several instruction-for-use manuals underestimate the depth down to as little as 4 cm [ 5 , 7 , 8 , 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…The 9.40 (SD, 0.64) cm mean insertion depth to the posterior nasopharyngeal wall in our study is in accordance with an earlier study measuring the insertion depth for a nasopharyngeal temperature probe [ 16 ]. Previously published guidelines described a similar insertion depth between 9 and 10 cm [ 6 ], while several instruction-for-use manuals underestimate the depth down to as little as 4 cm [ 5 , 7 , 8 , 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…Minimal data has been published regarding the depth of the nasopharynx. A study by Lim and Lee (21) from Korea demonstrated in a series of 200 individuals that the average distance from nostril to nasopharynx surface was 9.4 ± 0.6cm in females and 10.0 ± 0.5 cm in males. They also found that the average distance from philtrum to tragus (akin to measuring nostril to ear distance) in the same set of patients was 14.4 ± 0.5 cm in females and 15.1 ± 0.6 cm in males.…”
Section: Discussionmentioning
confidence: 97%
“…Minimal data has been published regarding the depth of the nasopharynx. A study by Lim and Lee [ 32 ] from Korea demonstrated in a series of 200 individuals that the average distance from nostril to nasopharynx surface was 9.4 ± 0.6 cm in females and 10.0 ± 0.5 cm in males. They also found that the average distance from philtrum to tragus (akin to measuring nostril to ear distance) in the same set of patients was 14.4 ± 0.5 cm in females and 15.1 ± 0.6 cm in males.…”
Section: Discussionmentioning
confidence: 99%